Effect of Hyamine-1622 Cationic Surfactant on Pertraction of Cerium (IV) Cations Through Emulsion Liquid Membranes - Kassem, Amany T.; Ali, Mahmoud M. S. (Journal of New Developments in Chemistry, 2021)
The present study aims to shed light directly towards the extraction of (IV) cerium ions using "liquid surfactant membrane" technology, "LSM" developed in the presence of synergistic cationic and nonionic materials. The effect of various factors such as Ce (IV) transport, synergistic surfactants, curing ratio, stir speed, temperature, and mixing time between the carrier and the cerium ion on the extraction rate was studied by LSM taking into account surfactant agents. The positive effect of benzethonium chloride "Hy-1622" on the extraction of cerium ion was demonstrated by LSMs technique. Experiments confirmed the efficiency of Hy-1622 chloride synergistically with Span 80/85 to extract cerium ions with LSMs technology for emulsions in the oil phase is critical as it determines the stability, viscosity and mass transfer resistance of the resulting emulsion. Besides, Hy-1622 chloride was found as a new cationic surfactant that appeared in FTIR characterization and surfactant was found to speed up the permeability process and accelerate the extraction rate due to electrostatic interaction with the carrier.
Keywords: Mohammad Tavakkoli; Shahid Chamran University of Ahvaz; Ahvaz; Iran.